Space charge in polyethylene under combined AC and DC voltages - Junwei Zhao; Chen, George; Lisheng Zhong (IEEE transactions on dielectrics and electrical insulation, 2014)
In contrast to extensive publication on the behavior of space charge in polymeric insulation materials subject to individual dc or ac voltages, space charge in the situation of composite voltages has not yet been reported. In this paper, the dynamics of space charge in polyethylene subjected to combined ac and dc voltages have been experimentally investigated using the pulsed electroacoustic technique. Results show that combined voltages could significantly enhance the space charge accumulation. The dc component voltage determines the charge accumulation in the bulk of polyethylene while ac component influences the charge density on the electrodes. The amount of charge in the bulk depends on the ratio between ac and dc voltage components. This result is important to understand the electrical performance of high voltage equipment where insulation may experience the combined ac and dc voltages.